Intelligibility of dialectal discourse: a priori attitudes - Aliūkaitė, Daiva (Lietuvių kalba, 2008)
The paper attempts to analyse the intelligibility of dialectal discourse. The analysis is based on anonymous questionnaires designed according to the principles suggested by Dennis R. Preston. The experiment was performed in several ethnic regions of Lithuania. Its overall sample includes 548 respondents. The a priori conceptualization of dialect intelligibility is related to a particular native polyglot horizon of the respondents. Only 1.39% of all female respondents and 2.39% of all male respondents a priori regard dialectal speech as completely unintelligible. Their comments help identify the image of dialectal speech within the following scenario: if I do not understand dialect X, no dialectal expression is intelligible. 69.44% of the female respondents and 59.62% of the male respondents think that dialectal speech is only partially intelligible. 19.44% of the female respondents and 20.77% of the male respondents claim that dialectal speech is nearly unintelligible. Thus dialectal speech could be described as partially intelligible due to its affinity to standard language (Mar6M10: part of the vocabulary is similar to that of standard language) or to the respondent's language (KauĄžM23: because the majority of words sound alike). Such arguments regarding the intelligibility of dialectal discourse are based on deductive reasoning (UkmDM32: since this language is nonetheless Lithuanian and therefore intelligible). Only 9.72% of the female respondents and 16.92% of the male respondents regarded dialectal speech as easily intelligible. However, such data is not enough to qualify dialectal speech as a speech code which does not require adequate knowledge and competence. Such distribution of the responses leads to a conclusion that young language users are not merely passive supporters of their own speech code. In fact, while qualifying dialectal speech as a distinct code of others mainly represented by the elder members of the speech community, young respondents place their own speech code in opposition to the described dialectal speech code. The data also shows that distinguishing young representatives of a particular region of Lithuania as those who understand the code of their native dialect better than any other member of the language community is hardly possible.
Keywords: none